Commodification of Merit: Reimaging God(s) through Public and Private Training Classes in Paiton Probolinggo - Mushafi Miftah (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) IAIN Pekalongan, 2017)
Material wealth, good health, and efforts to make money are central, but not solely, to the flourishing of religious commodifications. Pola-Pertolongan-Allah is a business-based-religious training which argues that strong beliefs in fate and luck are essential to the efficacy of the rituals, which is believed to generate ‘practical benefits’ for the participants of training. By paying for IDR500,000 – IDR1,500,000 / meeting for private class, and IDR150,000 /three hours for public classes, ‘the devotees’ will get also some kinds of bonus, including additional handbooks of tauhid, practical guide of various shalat patterns. PPA, by doing so, has successfully made the participant to be instrumental in performing meritorious acts to secure future happiness for themselves and their descendants, but still must depend on their fate and moral luck if they are to have the best possible outcomes. PPA, which operates with Multi-Level-Marketing recruitment system, stands in the increased commercialization of Muslim community in Probolinggo. This study finally figures out that commodified religious mode and technique of merit making could be subverted and employed to negotiate and express their religious-economic class identities.